Strategies to Reduce Speaking Anxiety in Supporting Effective Communication among Pharmacy Students at Borneo Citra Medika Health Polytechnic - Ahmad Nurwanto; Dwi Wulan Apriani (CV. ITTC INDONESIA, 2025)
Speaking anxiety is a major challenge for health students, particularly pharmacy students, in developing effective communication skills that are essential for their future professional practice. Communication competence is a crucial component of pharmacy education, as pharmacists are required to provide clear information, counselling, and health education to patients. High levels of speaking anxiety can hinder students’ ability to express their ideas confidently, both in academic settings and clinical practice. This study aimed to identify and analyze strategies to reduce speaking anxiety among pharmacy students and support effective communication. A pre-test and post-test experimental design was employed, involving 30 students from the Diploma III Pharmacy Program at Politeknik Kesehatan Borneo Citra Medika, South Kalimantan, Indonesia. Data were collected using structured questionnaires to measure speaking anxiety before and after the intervention, as well as students’ commonly used coping strategies. Data analysis was conducted using the Wilcoxon test to determine the differences in speaking anxiety levels before and after the intervention. The results indicated that relaxation techniques, peer support, and systematic practice through role-play and simulations were effective in reducing speaking anxiety. Careful preparation prior to presentations and constructive feedback from instructors were also associated with improved communication performance. These findings highlight the importance of integrating anxiety reduction strategies into the pharmacy curriculum to enhance students’ confidence and communication skills, thereby better preparing them to become effective health communicators in their professional practice